GNOA1 Gene Mutation in Children: A Case Report (Journal of Bangladesh College of Physicians and Surgeons, 2025)
GNOA1 gene mutations are rare genetic disorders linked to neurodevelopmental disorders in children. This case report describes the variable clinical manifestations of two unrelated children with GNOA1 gene mutations who were evaluated at a tertiary care hospital in Bangladesh. The first case presented with early-onset epilepsy along with movement disorders, while in the second case, movement disorders were observed without seizures. Both cases exhibited common features of global developmental delay. GNOA1 gene mutation was found in both cases using whole-exome sequencing. To our knowledge, these are indeed the first case report from Bangladesh..The findings from this case report contribute to the understanding of the diverse clinical spectrum of GNOA1 gene mutations and awareness of this variability is essential for accurate diagnosis, prognosis, and management.   J Bangladesh Coll Phys Surg 2025; 43: 250-252